PENGEMBANGAN BAHAN AJAR PPKN BERMUATAN NILAI TRADISI MENUGAL MASYARAKAT DAYAK KUHIN UNTUK MENUMBUHKAN SIKAP GOTONG ROYONG DAN TANGGUNG JAWAB SISWA KELAS III SDN 6 MENTENG - Gunawan; Ady Ferdian Noor; Asep Solikin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The declining spirit of cooperation and responsibility among elementary school students has become a critical issue in character education. Within PPKn learning that often remains conventional and abstract, the Dayak menugal tradition stands as a powerful yet underused source of local wisdom. This study aims to identify menugal values relevant to Grade III PPKn learning, develop culturally grounded teaching materials, assess their feasibility, and evaluate their effectiveness in strengthening cooperative and responsible behavior. Using a Research and Development design with the ADDIE model, the study involved 26 Grade III students at SDN 6 Menteng. Data were gathered through interviews, observations, documentation, questionnaires, and tests. Findings show that menugal embodies key values such as cooperation, collective responsibility, solidarity, teamwork, and ecological awareness, all suitable for integration into PPKn. The developed materials received expert validation above 80% and proved effective, producing moderate to high gains in students’ cooperative and responsible attitudes.